Simultaneous Spectrofluorometric Determination of Phenylalanine and Tryptophane Using Rank Annihilation Factor Analysis - Mansori, Ghobad; Asadpour, Saeid (Asian Journal of Chemistry, 2010)
The application of rank annihilation factor analysis (RAFA) to the analysis of fluorescence excitation-emission matrices of mixtures of phenylalanine and tryptophan is described. The input of rank annihilation factor analysis consists of two bilinear data matrices, i.e., one for unknown and one for the calibration sample. The excitation wavelength range was from 200- 300 nm and the emission was recorded from 310-800 nm. Phenylalanine and tryptophan were determined in the concentration range (0.1-1.5) × 103 μg mL-1 and 0.5-10 μg mL-1, respectively. To check the accuracy of the proposed method, several binary synthetic mixtures were analyzed successfully. No matrix effect was observed in mixture analysis, so a single external calibration sample was used for each analyte. The ability of rank annihilation factor analysis to quantify the studied compounds and the comparability of rank annihilation factor analysis results were evaluated by comparing them with those of partial least squares (PLS) regression as a standard firstorder calibration.